Resistance trend in bacteria isolated from corneal ulcers: A retrospective analysis from Pakistan - Naila Obaid; Ayesha Saeed; Sidra Abbas; Shaghufta Perveen; Hajira Younas (PLoS ONE, 2025)
Objective The purpose of this study is to isolate and characterize bacteria from corneal ulcers and screen them for multiple antibiotic resistance, contributing to understanding patterns of resistance and identifying effective treatment strategies. Design A retrospective study was conducted between January 2024 to August 2024 Subjects, participants and/or controls The study involved the isolation of pathogenic bacterial strains from 15 corneal ulcer samples. Methods, intervention, or testing We isolated and characterized bacterial strains from corneal ulcer samples, which were routinely collected at an ophthalmology clinic for suspected infectious corneal ulcers and examined their resistance to twenty-six routinely prescribed antibiotics. The bacterial species included methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa and E. coli among others. Antibiotic resistance patterns were assessed, with a focus on commonly used antibiotics such as ciprofloxacin, gentamycin, and vancomycin. Main outcome measures The study measured the healing rates of corneal ulcer patients, antibiotic resistance levels across bacterial strains, and specific treatment responses to various antibiotics. Results Thirteen out of fifteen corneal ulcer patients healed completely, while two patients developed full corneal opacity due to infection with P. aeruginosa. Significant differences in resistance were observed among the bacterial strains. MRSA exhibited the highest resistance levels, particularly to multiple antibiotics. Ciprofloxacin and gentamycin were less effective against the isolated strains, while vancomycin showed reduced resistance, against Gram-positive bacteria. Both ciprofloxacin and co-trimoxazole exhibited strong connections with multiple bacterial strains, indicating high resistance. Conclusion This study underscores the need for ongoing surveillance of antibiotic resistance patterns to guide treatment approaches and slow the spread of resistant bacteria. It also highlights the importance of developing new antibiotics and alternative therapies, with an emphasis on understanding the molecular mechanisms behind resistance to combat the global health posed by antibiotic-resistant infections.